2020
DOI: 10.1186/s13075-020-2112-7
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor signals attenuate lung fibrosis in the bleomycin-induced mouse model for pulmonary fibrosis through increase of regulatory T cells

Abstract: Background: Interstitial lung disease (ILD) is a serious complication of connective tissue diseases (CTDs). Although immune dysregulation triggered by genetic and environmental factors is thought to provoke inflammation and subsequent fibrosis, precise mechanisms of these processes remain unclear. Recent reports suggest that activation of aryl hydrocarbon receptor (AhR) signals by various ligands such as tryptophan derivatives can induce hyperimmune responses and are involved in autoimmunity. We investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…A natural AhR agonist norisoboldine promoted Tregs differentiation through regulating glycolysis and NAD+/SIRT1/SUV39H1/H3K9me3 signaling pathway during colitis development [ 106 ]. A recent study indicated a role of AhR signal in regulating Tregs functions during fibrogenic responses [ 107 ]. Bleomycin-challenged mice with treatment of FICZ, a natural AhR ligand, exhibited increased number of Tregs with attenuated lung fibrosis, suggesting a therapeutic potential of targeting AhR for treating fibrotic diseases [ 107 ].…”
Section: Adaptive Immune Cells In the Pathogenesis Of Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…A natural AhR agonist norisoboldine promoted Tregs differentiation through regulating glycolysis and NAD+/SIRT1/SUV39H1/H3K9me3 signaling pathway during colitis development [ 106 ]. A recent study indicated a role of AhR signal in regulating Tregs functions during fibrogenic responses [ 107 ]. Bleomycin-challenged mice with treatment of FICZ, a natural AhR ligand, exhibited increased number of Tregs with attenuated lung fibrosis, suggesting a therapeutic potential of targeting AhR for treating fibrotic diseases [ 107 ].…”
Section: Adaptive Immune Cells In the Pathogenesis Of Fibrosismentioning
confidence: 99%
“…A recent study indicated a role of AhR signal in regulating Tregs functions during fibrogenic responses [ 107 ]. Bleomycin-challenged mice with treatment of FICZ, a natural AhR ligand, exhibited increased number of Tregs with attenuated lung fibrosis, suggesting a therapeutic potential of targeting AhR for treating fibrotic diseases [ 107 ]. Tregs also exerted protective functions against coxsackievirus B3-induced cardiac fibrosis via secretion of IL-10, an important regulatory cytokine [ 108 ].…”
Section: Adaptive Immune Cells In the Pathogenesis Of Fibrosismentioning
confidence: 99%
“…Sections (5 mm) of paraffin-embedded lung tissues were stained with hematoxylin and eosin (H&E) according to standard histological procedures and optical observation of the microscopic lung structure was performed blindly by an expert pathologist. Lung inflammation was assigned a score from 0 to 3 based on the absence(0) or presence to a mild 1 , moderate 2 , severe 3 degree of focal thickening of alveolar membranes, congestion, and interstitial and intra-alveolar neutrophil infiltration. A total cumulative histology score was determined 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The adverse effects of chemotherapy limit the quality of life and survival of cancer patients. Among them, kidney failure 1 , interstitial pneumonia 2 , and allergic pneumonitis 3 feature an over-activated immune system and inflammation, and often require permanent cessation of the ongoing therapy, including cisplatin, bleomycin, and immune checkpoint inhibitors (ICIs) 4 . Glucocorticoids are considered as fundamental choice of drugs for the prevention and treatment for such inflammatory adverse events 1 , 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, AhR is widely expressed in immune cells where the activated receptor can tip the balance regulatory and inflammatory T cells in favor of the former subset. Administration of AhR agonists alleviated immunopathology in various animal models, such as experimental autoimmune encephalomyelitis, experimental colitis (Quintana et al, 2008) and, recently, a model of pulmonary fibrosis (Takei et al, 2020). Kyn is also a potent vasodilator of systemic arteries and has been found to be significantly increased in pulmonary arterial hypertension patients.…”
Section: Tcz and Tryptophan (Trp) Catabolismmentioning
confidence: 99%